Analysis of Sebelas Maret University Students Insight of Cosmetic Waste Management that has Hazardous and Toxic Content - Hashfi Hawali Abdul Matin; Muhammad Amjad Hamy Faqiih; Muhammad Yusuf Muharram Bayu Aji; Silvi Puspita Sari; Ulfi Hanum; Vania Maharani Rizky Pratiwi (Diponegoro University, 2022)
Cosmetics contain chemicals including formaldehyde, fragrance and even heavy metals such as lead or mercury. So indirectly cosmetic packaging waste must also contain harmful chemicals and belong to waste B3. Toxic hazardous material waste (waste B3) is waste that contains harmful and toxic substances, so that it can directly or indirectly pollute and damage the environment, disrupt health, and threaten the survival of humans and other organisms. The awareness of students of Universitas Sebelas Maret Surakarta towards B3 waste management can be seen from their understanding of the dangers and how to handle B3 waste in the environment around the residence. An understanding of B3 waste is important in shaping a person's attitude or behavior towards the sustainability of the surrounding environment. The purpose of this study is to find out how much information and knowledge is owned by students of Universitas Sebelas Maret Surakarta related to the management of B3 cosmetic waste in the surrounding environment. The analysis method used in this study is a descriptive analysis method whose descriptive explanation of the data obtained regarding the knowledge of Sebelas Maret University students on B3 cosmetic waste. The data collected is in the form of primary data conducted through questionnaires and secondary data from valid sources. The results showed that the knowledge of students of Universitas Sebelas Maret Surakarta about B3 cosmetic waste was relatively good. However, for B3 waste management is still not good enough proven from 50 respondents only 30 respondents who stated that using the 3R method (reuse, reduce, recycle) on B3 cosmetic waste, the remaining 20 respondents answered never or just thrown away and there was only one respondent who ever sent B3 cosmetic waste to the authorities sent to the installation